2005
DOI: 10.1262/jrd.16089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Stress on the Redox Status in the Oviduct and Early Embryonic Development in Mice

Abstract: Abstract. This study examined the association between redox status in the oviduct and early embryonic death in heat-stressed mice. In Experiment 1, non-pregnant mice were heat-stressed at 35 C with 60% relative humidity for 12, 24, or 36 h, and the maternal redox status was verified by measuring the levels of reactive oxygen species (ROS) and free radical scavenging activity (FRSA) in the oviduct, and thiobarbituric acid reactive substances (TBARS) and glutathione peroxidase (GSHPx) activity in the liver. In E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 34 publications
4
44
0
3
Order By: Relevance
“…Additionally, heat stress was found to change the numbers of follicles and their diameters [6] and also to modify the fatty acid [6] and protein [18] composition of the porcine oocyte plasma membrane. Furthermore, heat stress induces reactive oxygen species and results in apoptosis of granulosa cells in mice and rats [19,20]. As reported in previous bovine studies [6][7][8], the present results clearly showed a negative relationship between developmental competence of porcine oocytes and atmospheric temperatures.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, heat stress was found to change the numbers of follicles and their diameters [6] and also to modify the fatty acid [6] and protein [18] composition of the porcine oocyte plasma membrane. Furthermore, heat stress induces reactive oxygen species and results in apoptosis of granulosa cells in mice and rats [19,20]. As reported in previous bovine studies [6][7][8], the present results clearly showed a negative relationship between developmental competence of porcine oocytes and atmospheric temperatures.…”
Section: Discussionsupporting
confidence: 86%
“…For example, exposing zygotes to heat shock has resulted in early embryonic loss, in association with increased hydrogen peroxide concentrations and reduced levels of GSH within the embryos (Ozawa et al 2002). Hyperthermia enhances the production of ROS in the mouse liver (Ozawa et al 2004) and oviduct (Matsuzuka et al 2005), shifting the redox status toward oxidative stress. In addition, in vitro supplementation of GSH or GSH ester reduced the effect of heat shock on viability of mouse embryos (Aréchiga et al 1995), while inhibition of GSH synthesis aggravated the deleterious effect of heat stress on the oocyte developmental capacity .…”
Section: Discussionmentioning
confidence: 99%
“…For example, heat exposure of cattle on the day of artificial insemination compromises pre-implantation embryo development in vivo (Ealy et al 1993). Previous reports from our group have shown that maternal hyperthermia for 12 h soon after mating strongly disturbs normal embryonic development both in vitro (Ozawa et al 2002, Matsuzuka et al 2005a and in vivo (Ozawa et al 2003). The present results are consistent with those of previous studies, in that heat exposure of mated mice for 12 h severely compromised normal embryonic development, as determined by the blastocyst formation rate and the cell numbers in the blastocysts (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent reports have demonstrated that culturing zygotes at high temperatures, within the physiological range, in hyperthermic cows (40.5 8C) for 12 h did not alter subsequent development to the blastocyst stage (Ryan et al 1992. Our previous study has also indicated that in vitro exposure of zygotes to high temperature, mimicking the average rectal temperature of hyperthermic mice (39.5 8C), does not alter the blastocyst development rate, whereas maternal heat exposure for 12 h soon after mating drastically arrests subsequent embryonic development and is accompanied by increased H 2 O 2 levels, decreased GSH levels (Ozawa et al 2002) and damaged genomic DNA in the embryos, as assessed by elongation of the ladder tail in a comet assay, which is typical of ROS-mediated injury (Matsuzuka et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation